THE ROLE OF SOCIAL SUPPORT ON THE STUDENT ADVERSITY QUOTIENT IN ISLAMIC BOARDING SCHOOL - Muhammad Fahrudin Aziz; Mayreyna Nurwardani (UIN Sunan Kalijaga, 2021)
Students who live in boarding schools often face different challenges, including strict rules in the dormitory, limited interaction with family, and the ability to deal with adversity in their daily lives. This research aimed to determine the correlation between social support and adversity quotient on Islamic Senior High School